Recomposição dos rituais contemporâneos : a peregrinação - Helena Vilaça (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2007)
Pilgrimage is considered in this article as one of the most representative phenomena of contemporary religious rituality. This approach includes the traditional religious tourism, whose rituals are predictable and institutionally supported as well as the intimate “voyage” in the sense of a reflection of individual religious experience and practice. Somehow paradox, pilgrimages have contributed, on one hand, to the reinforcement of traditional churches and the reproduction of their members practices and, on the other, to the expression of individual and privatized religiosity, close to the new conceptual perspectives on spirituality